2008
DOI: 10.1148/radiol.2483071686
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double-Strand Breaks after Percutaneous Transluminal Angioplasty

Abstract: GammaH2AX focus formation can be used to determine in vivo induction of DNA DSBs after PTA. DSB repair capacity is compromised in patients who undergo PTA of lower limb arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…A linear dependence of DSB induction related to dose-area product (r = 0.993) was found among patients who had undergone percutaneous transluminal angioplasty of the arteries of the lower extremity. The DSB were repaired quickly, the initial values measured prior to exposure (0.04 foci/cell) were not completely achieved (0.07 foci/cell) within 24 hours, however [23]. An increase in DSB was likewise shown after cardiac catheterization in children; the induced γ-H2AX foci in the low-dose range up to 5 mGy, however, correlated non-linearly with the blood dose determined using Monte Carlo simulation.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…A linear dependence of DSB induction related to dose-area product (r = 0.993) was found among patients who had undergone percutaneous transluminal angioplasty of the arteries of the lower extremity. The DSB were repaired quickly, the initial values measured prior to exposure (0.04 foci/cell) were not completely achieved (0.07 foci/cell) within 24 hours, however [23]. An increase in DSB was likewise shown after cardiac catheterization in children; the induced γ-H2AX foci in the low-dose range up to 5 mGy, however, correlated non-linearly with the blood dose determined using Monte Carlo simulation.…”
mentioning
confidence: 89%
“…In the case of blood lymphocytes, a range of 0.05 -0.15 per cell have been described ( • " Table 1). DSB induction results in a rapid increase of measurable foci; in some studies the highest values have been measured 5 minutes after exposure [12,13,23]. This quantity of radiation-induced foci demonstrate a dependence on the dose, which in most in-vitro and in-vivo studies was linear [7, 9,13,23,33].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro dose-response curves of ␥-H2AX foci in other cellular systems such as fibroblasts are reported in the literature to be linear, but a detailed analysis in the low-dose range as performed in present study is not available. 14,16,36,37 Data are also lacking relative to the dose-response curve of ␥-H2AX foci in lymphocytes based on in vitro irradiation of whole-blood samples, simulating the in vivo x-ray exposure. To elucidate the effect of the cell environment on foci formation in lymphocytes, we also determined the dose response after in vitro irradiation of isolated lymphocytes; the biphasic behavior and low-dose hypersensitivity observed after whole-blood irradiation were much less pronounced for isolated lymphocytes (data not shown).…”
Section: Beels Et Al Radiation Risk In Pediatric Cardiac Catheterizationmentioning
confidence: 99%
“…11 Small studies 10,12 have suggested an association between contrast media and increased DNA DSBs in individuals exposed to low-dose radiation but not necessarily highdose radiation.…”
Section: Iodinated Contrast Mediamentioning
confidence: 99%